The Effect of Capital Market and Public Savings on Indonesia's Economic Growth - Binanga, Angga; Apridar; Seftarita, Chenny (MSJ : Majority Science Journal, 2024)
This study analyzes the impact of the capital market and public savings on economic growth in Indonesia using panel data from 34 provinces over the period 2016 to 2022. It aims to address the gaps in previous research, which showed inconsistent results regarding the effect of real sector investment on economic growth. Through multiple linear regression, this study finds that the capital market and public savings have a positive and significant influence on economic growth. These findings suggest that increasing capital accumulation in the capital market and public savings in banks can be an effective strategy to stimulate economic growth. The best model used in this study is the Fixed Effect Model, selected based on the Chow and Hausman tests. The coefficient of determination indicates that the capital market and public savings variables can explain the variation in economic growth significantly. This study contributes new insights by using data on domestic investor assets at the provincial level and offers policy recommendations to enhance public participation in the capital market and banking sector. The limitations of this study lie in the data coverage, which is restricted to Indonesia and spans a seven-year period, thus caution is needed when generalizing the findings to other countries or longer timeframes. Future research is encouraged to include additional variables and expand the geographical and temporal scope of the analysis.